Strategy for Improving the Government System Index Bekasi City Electronics Based - Indrijantoro, Widodo; Irwansyah, Iwan (Asian Journal of Community Services, 2024)
The government realizes the important role of SPBE to support all development sectors. Efforts to encourage the implementation of SPBE have been made by the government by issuing laws and regulations which mandate the need for the implementation of information systems or SPBE. So far, ministries, institutions and regional governments have implemented SPBE individually according to their capacity, and achieved levels of SPBE progress that vary widely nationally. To build synergy in the implementation of SPBE that has legal force between ministries, institutions and regional governments, a National SPBE Master Plan is needed which is used as a guide for Central Agencies and Regional Governments to achieve an integrated SPBE. Research is carried out using a descriptive method which attempts to describe the object or subject as it is, with the aim of accurately describing the facts and characteristics of the object being studied.